Evaluasi Standar Pelayanan Minimal Rekam Medis di RSUD Panembahan Senopati Bantul - Kori Puspita Ningsih; Sigid Nugroho Adhi (Indonesian of Health Information Management Journal (INOHIM), 2020)
AbstractOne of the vital parts of the hospital is the medical record. The minimum service standard for medical records is a reference in managing medical records. The results of preliminary data collection at Panembahan Senopati Bantul Hospital did not reveal that there were incomplete medical records within 1x24 hours. This shows that Panembahan Senopati Bantul Hospital has not reached the standard of Permenkes No. 129 of 2008. The purpose of this study is to meet the minimum service standards for medical records. Descriptive research method with a qualitative approach. Primary data were obtained from interviews with informants. Secondary data were obtained from observation and documentation study related to the SPM report in the field of medical records. The results showed that the Panembahan Senopati Bantul Regional Hospital conducted a study of SPM medical records by utilizing data from the RS SIM. The SPM report of medical records to the Head of Quality and Clinical Audit Section to be used as a data source for making RS SPM reports. Of the four indicators of SPM medical records, there are 2 indicators (50%) that have not reached the standard, namely completeness of medical records and informed consent. Efforts are made to improve the completeness of medical records and informed consent is to provide feedback to doctors every 3 months through the medical service sector and the medical committee regarding the results of completing medical records and complete components according to the doctor's name.Keyword: evaluation, minimum service standards, medical recordAbstrakSatu diantara bagian vital rumah sakit adalah rekam medis. Standar pelayanan minimal rekam medis merupakan acuan dalam pengelolaan rekam medis. Hasil pengambilan data awal di RSUD Panembahan Senopati Bantul diketahui bahwa terdapat rekam medis yang tidak lengkap dalam waktu 1x24 jam. Hal ini menunjukkan RSUD Panembahan Senopati Bantul belum mencapai standar Permenkes No 129 Tahun 2008. Tujuan penelitian ini untuk mengevaluasi standar pelayanan minimal rekam medis. Metode penelitian desktiptif dengan pendekatan kualitatif. Data primer diperoleh dari hasil wawancara dengan informan. Data sekunder diperoleh dari observasi dan studi dokumentasi terkait laporan SPM bidang rekam medis. Hasil penelitian menunjukkan RSUD Panembahan Senopati Bantul melalukan kegiatan pengumpulan data SPM rekam medis dengan memanfaatkan data dari SIM RS. Laporan SPM rekam medis kepada Kepala Seksi Mutu dan Audit Klinik untuk digunakan sebagai salah satu sumber data pembuatan laporan SPM RS. Dari keempat indikator SPM rekam medis terdapat 2 indikator (50%) yang belum mencapai standar yaitu kelengkapan rekam medis dan informed consent. Upaya yang dilakukan untuk meningkatkan kelengkapan rekam medis dan informed consent adalah dengan memberikan feedback kepada dokter setiap 3 bulan sekali melalui bidang pelayanan medis dan komite medis terkait hasil kelengkapan rekam medis dan komponen yang tidak lengkap per nama dokter.Kata Kunci: evaluasi, standar pelayanan minimal, rekam medis